An overview on the photoluminescence emission in ZNO single crystal. A joint experimental and theoretical analysis - Lima, Renata C.; Andrés, J.; Sambrano, Júlio R. [UNESP]; Longo, Valéria M. [UNESP]; Macário, Leilane R. [UNESP]; Espinosa, José W. M.; Pizani, Paulo S.; Varela, José A. [UNESP]; Longo, Elson [UNESP] (My University, 2012)
The purpose of the present chapter is to join both the experimental and theoretical results to explain the different responses of photoluminescence (PL) emission at room temperature of ZnO powders by using different structural order-disorder effects, associated with intermediate and short range defects. Recent theoretical and experimental analyzing the crystal and surface structures, electronic and PL properties ZnO-based materials have been presented. In addition, the synthetic methods, with particular attention to hydrothermal conventional and microwave assisted hydrothermal procedures, characterization techniques, as well as crystal growth process has been reviewed. The two synthesis methods used in the ZnO powders preparation, conventional hydrothermal and microwave hydrothermal, suggest different defects formation, which can be an indicative of different conformations into the hexagonal structure (wurtzite) during the ZnO growth. This review focuses on studies that employ electronic structure calculations, which primarily concentrate on using density functional theory (DFT) to understand PL behavior. DFT calculations, at the B3LYP level, have been combined with the results obtained by using X-ray diffraction, Raman, and photoluminescence techniques The theoretical results indicate that the key factor controlling the electronic behavior can be associated with a symmetry breaking process, creating localized electronic levels between the valence and conduction bands. These defects are associated structural disorder generated by the presence of distortions in the ideal constituent clusters of these materials [ZnO4] and [ZnO3. VzO]. © 2012 Nova Science Publishers, Inc.
Keywords: Conventional hydrothermal and microwave assisted hydrothermal methods; Photoluminescence; Theoretical calculations; Zinc oxide